(untitled) (Journal of the College of Basic Education, 2022)
The Pseudomonas aeruginosa strain grows optimally in the temperature of 40ºC and pH 7.The lipase was extracted and purified by precipitation with 45% saturation of ammonium sulfate, dialysis and filtration chromatography by Sephadex G-150, two peaks of protein appeared in last step, the lipase activity was observed in second peak. The purified lipase has specific activity 3.67 unit/mg with protein concentration 0.27 mg/ml. Analysis of purified lipase was done by HPLC, the individual peak was identified by comparing the retention time of peak with standard. Pseudomonas aeruginosa lipase was treated with different concentration of plant extract to determine their effect on the production and activity of this enzyme. The methanolic extract varied in their effect Quercus infectoria reduced the effectiveness of the enzyme activity more than Trigoella foenum graecum.